Molecular Evidence of Interhuman Transmission of Pneumocystis Pneumonia among Renal Transplant Recipients Hospitalized with HIV-Infected Patients - Meja Rabodonirina; Philippe Vanhems; Sandrine Couray-Targe; René-Pierre Gillibert; Christell Ganne; Nathalie Nizard; Cyrille Colin; Jacques Fabry; Jean-Louis Touraine; Guy van Melle; Aimable Nahimana; Patrick Francioli; et al. (Emerging Infectious Diseases, 2004)
Ten Pneumocystis jirovecii pneumonia (PCP) cases were diagnosed in renal transplant recipients (RTRs) during a 3-year period. Nosocomial transmission from HIV-positive patients with PCP was suspected because the these patients shared the same hospital building, were not isolated, and were receiving no or suboptimal anti-PCP prophylaxis. P. jirovecii organisms were typed with the multitarget polymerase chain reaction–single-strand conformation polymorphism method. Among the 45 patients with PCP hospitalized during the 3-year period, 8 RTRs and 6 HIV-infected patients may have encountered at least 1 patient with active PCP within the 3 months before the diagnosis of their own PCP episode. In six instances (five RTRs, one HIV-infected patient), the patients harbored the same P. jirovecii molecular type as that found in the encountered PCP patients. The data suggest that part of the PCP cases observed in this building, particularly those observed in RTRs, were related to nosocomial interhuman transmission.